Photo-thermal catalytic filter screen without external heat source and application of photo-thermal catalytic filter screen in removal of peculiar smell gas in air

By developing a photothermal catalytic filter without an external heating source, using copper-bismuth bimetal site polymerization of carbon nitride-titanium dioxide composite catalyst, the existing photocatalyst technology has solved the problem of low efficiency and high cost in indoor air odor removal, and achieved the effect of efficient removal of a variety of gaseous pollutants.

CN119755742APending Publication Date: 2025-04-04SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510040675.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing photocatalyst technology has low efficiency, high cost and limited catalytic purification capabilities in indoor air odor removal, especially the removal effect of odor gases such as methylmercaptan and isovaleric acid.

Method used

A photothermal catalytic filter without external heating source was developed, using copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst, prepared by modified copper metal precursor solution and urea and other materials, combining physical adsorption and photothermal catalytic purification functions.

Benefits of technology

It has achieved efficient removal of various gaseous pollutants such as toluene, methylmercaptan, isovaleric acid, acetic acid and other gaseous pollutants in indoor air under different temperatures, humidity and pollutant concentrations. It has a long-lasting and stable purification effect, and is simple in preparation process, low cost, and is convenient for commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119755742A_ABST
    Figure CN119755742A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of air pollution abatement, in particular to a photo-thermal catalytic filter screen without an external heat source and application of the photo-thermal catalytic filter screen in removal of peculiar smell in air, and the photo-thermal catalytic filter screen is prepared by loading a copper-bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst on a carrier; the carrier is any one of activated carbon honeycomb cotton and non-woven fabric. According to the photo-thermal catalytic filter screen, physical adsorption and photo-thermal catalytic purification functions are integrated, synergism of adsorption and catalytic action is achieved, and various gas pollutants such as volatile organic compounds and peculiar smell gas in indoor air can be efficiently removed without external heating; the preparation process of the catalyst and the filter screen thereof is simple and convenient, the cost is low, and commercial scale production is facilitated. Therefore, the photo-thermal catalytic filter screen has a wide application prospect in the field of indoor air purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air pollution control, and in particular to a photothermal catalytic filter screen that does not require an external heat source and its application in removing odorous gases from the air. Background Art

[0002] Indoor air pollution refers to the mixing of harmful chemicals, biological pollutants or radioactive substances in the air in a closed or semi-closed indoor environment, and the concentration of these pollutants exceeds the health standard. Chemical pollutants mainly come from formaldehyde, toluene, mercaptan, sulfide, indole, etc. released by paint, decorations, domestic garbage and furniture. In newly renovated houses, the plywood and fiberboard of furniture may emit formaldehyde for a long time. There are also combustion products, such as carbon monoxide produced when using gas or charcoal fire for heating and cooking. These pollutants can cause symptoms such as eye discomfort, headache, dizziness, cough, and asthma. Long-term exposure may lead to more serious diseases such as cancer and immune system diseases.

[0003] Photocatalyst technology is a technology that uses semiconductor materials to produce strong oxidizing substances under the irradiation of light, thereby decomposing organic compounds, inorganic compounds, bacteria and viruses in the air. When the photon energy is equal to or greater than the bandgap width of the photocatalyst material, the electrons in the valence band will be excited to jump to the conduction band, and corresponding electron holes will be generated in the valence band. After the electrons and holes migrate to the surface, they react with the water and oxygen adsorbed on the surface to generate strong oxidizing substances such as hydroxyl free radicals and superoxide anions. These substances can effectively decompose various organic compounds and some inorganic substances, and ultimately degrade them into harmless small molecules such as water and carbon dioxide, and can also destroy the cell membrane of bacteria and the protein carrier of coagulated viruses. Therefore, photocatalysts can effectively decompose harmful volatile organic compounds such as formaldehyde, benzene, and toluene, and can also kill bacteria and viruses in the air and remove odors. They have been widely used in the field of indoor air purification. For example, patent technical solution CN202211312562 discloses a photocatalyst coating structure for the production of a photocatalyst air purification layer; and patent technical solution CN107930620A discloses a method for preparing a titanium dioxide air purification photocatalyst loaded with ultra-small precious metals.

[0004] However, these existing technical solutions still have problems such as insufficient purification efficiency of photocatalysts, and the efficiency of light energy utilization needs to be improved; photocatalysts generally rely on precious metals, and the high cost makes them difficult to apply commercially; the catalytic effect of photocatalysts on pollutants lacks universality. Although photocatalysts can effectively remove formaldehyde and some volatile organic compounds, they are not effective in removing odorous gases such as methyl mercaptan and isovaleric acid.

[0005] Therefore, according to the above-mentioned related technologies, there is an urgent need to develop a photothermal catalytic filter that does not require an external heat source and its application in removing odorous gases from the air. Summary of the invention

[0006] In view of this, the purpose of the present invention is to propose a photothermal catalytic filter that does not require an external heat source and its application in removing odorous gases from the air, so as to solve the problems of low photocatalyst efficiency, high production cost and limited catalytic purification capacity in the prior art for removing odor from indoor air.

[0007] Based on the above objectives, the present invention provides a photothermal catalytic filter that does not require an external heat source and its application in removing odorous gases from the air.

[0008] A photothermal catalytic filter screen without external heat source comprises the following raw materials in parts by weight: 1 part of copper-bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst and 10-100 parts of a carrier;

[0009] The copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst is prepared from urea, a copper metal precursor solution, a bismuth metal precursor, and titanium dioxide;

[0010] The copper metal precursor solution is any one of a common copper metal precursor solution and a modified copper metal precursor solution;

[0011] The modified copper metal precursor solution is prepared from a copper metal precursor, citric acid, and deionized water;

[0012] The copper metal precursor is any one of copper nitrate, copper hydroxide and copper chloride;

[0013] The carrier is any one of activated carbon honeycomb cotton and non-woven fabric.

[0014] Preferably, the bismuth metal precursor is any one of bismuth nitrate, bismuth sulfate, bismuth chloride, and bismuth basic carbonate.

[0015] Preferably, the preparation method of the copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst is as follows:

[0016] Step A1: dissolving citric acid and a copper metal precursor in deionized water, stirring for 30-60 minutes, reacting in a polytetrafluoroethylene container at 150-200° C. for 4-8 hours, filtering impurities and collecting the supernatant after centrifugation to obtain a modified copper metal precursor solution; adding 5 g of the copper metal precursor to 50 mL of water, stirring evenly to obtain a common copper metal precursor solution;

[0017] Step A2: adding urea and copper metal precursor solution to deionized water, stirring for 3-6 hours and then evaporating to dryness, then calcining, and naturally cooling to obtain copper metal site polymerized carbon nitride;

[0018] Step A3: Add 0.5-1.5 g of bismuth metal precursor to 10 mL of deionized water and stir to obtain a bismuth metal precursor solution;

[0019] Step A4: adding copper metal site polymerized carbon nitride and a sacrificial agent to deionized water, and then dripping a bismuth metal precursor solution while stirring after ultrasonic treatment, stirring for 5-10 minutes, and then sequentially irradiating and centrifuging, and finally washing and drying the solid to obtain copper bismuth bimetallic site polymerized carbon nitride;

[0020] Step A5: add copper-bismuth bimetallic site-polymerized carbon nitride and titanium dioxide into a solvent and stir evenly, then perform ultrasonic treatment, and evaporate to dryness to obtain a copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst.

[0021] Preferably, the mass ratio of citric acid, copper metal precursor and deionized water in step A1 is 1-2:5:50.

[0022] Preferably, the mass ratio of urea to copper metal precursor solution in step A2 is 10-12:20-24;

[0023] The heating rate during the calcination treatment in step A2 is 5-10°C / min, the calcination temperature during the calcination treatment is 450-600°C, and the calcination time during the calcination treatment is 2-3h.

[0024] Preferably, the amount ratio of deionized water, copper metal site polymerized carbon nitride, sacrificial agent, and bismuth metal precursor solution in step A4 is 100-150 mL: 1 g: 20-21 g: 2 mL;

[0025] The sacrificial agent in step A4 is any one of ethanol, methanol, isopropanol, and n-propanol;

[0026] In step A4, the power of the ultrasonic treatment is 20-40 kHz, the frequency of the ultrasonic treatment is 60-70 W, and the duration of the ultrasonic treatment is 5-10 min;

[0027] The light intensity during the irradiation treatment in step A4 is 100 mW / cm 2 The irradiation time during the irradiation treatment is 3 hours;

[0028] The relative centrifugal force during the centrifugal treatment in step A4 is 400×g, and the centrifugal time during the centrifugal treatment is 10-20 min.

[0029] Preferably, the solvent in step A5 is any one of methanol, deionized water, ethanol, and propanol;

[0030] The mass ratio of the copper-bismuth bimetallic site-polymerized carbon nitride to titanium dioxide in step A5 is 1:100-200;

[0031] The power of the ultrasonic treatment in step A5 is 20-40kHz, the frequency of the ultrasonic treatment is 60-70W, and the duration of the ultrasonic treatment is 1-2h.

[0032] Preferably, the photothermal catalytic filter preparation method is as follows:

[0033] Step S1: adding an aqueous dispersion medium, triethanolamine, glycerol and a mechanical property improver to deionized water, stirring at 60-90° C. for 0.5-1 h, adding a copper-bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst, stirring at 60-90° C. for 0.5-1 h, adding an adhesive and continuing to stir at 60-90° C. to obtain a coating liquid;

[0034] Step S2: immerse the carrier in the coating liquid, take out the carrier after 1-2 hours, and dry it at 40-80° C. for 1-4 hours to obtain a photothermal catalytic filter.

[0035] Preferably, the aqueous dispersion medium in step S1 is any one or more of ethanol, methanol, isopropanol, and propylene glycol;

[0036] The mechanical property improver in step S1 is 40%-70% alkaline silica sol;

[0037] The alkaline silica sol has a pH of 8-11;

[0038] The adhesive in step S1 is any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, and polyacrylamide;

[0039] The mass ratio of the deionized water, aqueous dispersion medium, triethanolamine, glycerol, mechanical property improver, copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst, and adhesive in step S1 is 150-200:20:1:1:10:2:5;

[0040] The mass ratio of the carrier to the coating liquid in step S2 is 3-9.4:175-225.

[0041] A photothermal catalytic filter that does not require an external heat source and its application in removing odorous gases from the air can be used to efficiently remove toluene, methyl mercaptan, isovaleric acid, acetic acid and odorous gases in indoor air.

[0042] Beneficial effects of the present invention:

[0043] The present invention provides a photothermal catalytic filter that does not require an external heat source and its application in removing odorous gases from the air. Since the photothermal catalyst developed by the present invention has highly dispersed copper-bismuth bimetallic synergistic active sites, the photothermal conversion performance of the copper-bismuth bimetallic site polymerized carbon nitride photothermal excitons is effectively enhanced by introducing a multi-carbon structure.

[0044] The composite catalyst composed of copper-bismuth bimetallic site-polymerized carbon nitride and titanium dioxide exhibits excellent component synergistic effect, and an efficient electron transfer channel is formed between the components, thereby showing a wide range of purification capabilities and efficient removal performance for various indoor gaseous pollutants such as toluene, methyl mercaptan and isovaleric acid.

[0045] The photothermal catalytic filter of the present invention integrates physical adsorption and photothermal catalytic purification functions, realizes the synergy of adsorption and catalysis, and can stably and efficiently remove various gaseous pollutants such as volatile organic compounds and odorous gases in indoor air without external heating under different temperature, humidity and pollutant concentration conditions, showing long-lasting and stable purification efficiency.

[0046] Moreover, the preparation process of the catalyst and the filter screen of the present invention is simple and low in cost, and is convenient for commercial scale production. Therefore, the photothermal catalytic filter screen of the present invention has a wide application prospect in the field of indoor air purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 The graphs of toluene conversion rate (a), methyl mercaptan conversion rate (b), isovaleric acid conversion rate (c), and acetic acid conversion rate (d) of the photothermal catalytic filter prepared by the present invention changing with time;

[0049] Figure 2 This is a field emission scanning electron microscope image of the copper-bismuth bimetallic site-polymerized carbon nitride prepared by the present invention;

[0050] Figure 3 This is a field emission scanning electron microscope image of the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared by the present invention;

[0051] Figure 4 A high-resolution transmission electron microscopy image of the copper-bismuth bimetallic site-polymerized carbon nitride prepared by the present invention;

[0052] Figure 5This is a photo of the photothermal catalytic filter prepared by the present invention;

[0053] Figure 6 The test diagrams are the initial reaction cycle stability (a) and the reaction cycle stability after water washing and regeneration (b) of the photothermal catalytic filter of the present invention for methyl mercaptan. DETAILED DESCRIPTION

[0054] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0055] Example 1: A method for preparing a photothermal catalytic filter without an external heat source is as follows:

[0056] S1: 1 g of citric acid and 5 g of copper nitrate were dissolved in 50 mL of deionized water, stirred for 30 min, and reacted in a polytetrafluoroethylene container at 150 ° C for 4 h. The solution was then centrifuged to remove large particles, and then the solid impurities were further filtered using an aqueous microporous filter membrane. Finally, the solution was dialyzed using a dialysis bag for 6 h, and the impurities were filtered and the supernatant was collected to obtain a modified copper metal precursor solution;

[0057] S2: 10 g urea and 20 g modified copper metal precursor solution were added to 100 mL deionized water, stirred for 3 h, dried in a rotary evaporator for 1 h, then heated to 450 °C at 5 °C / min, calcined for 2 h, and cooled naturally to obtain copper metal site polymerized carbon nitride;

[0058] S3: Add 0.5 g of bismuth nitrate to 10 mL of deionized water, stir and dissolve to obtain a bismuth metal precursor solution;

[0059] S4: 1 g of copper metal site polymerized carbon nitride and 20 g of ethanol were added to 100 mL of deionized water. After ultrasonic treatment at 20 kHz and 60 W for 5 min, 2 mL of bismuth metal precursor solution was added dropwise while stirring. After stirring for 5 min, the mixture was first heated at 100 mW / cm 2 The solid was irradiated for 3 h at room temperature, centrifuged at 400 × g for 10 min, and finally the solid was washed twice with ethanol and deionized water, respectively, and dried at 80 ° C for 24 h to obtain copper-bismuth bimetallic site polymerized carbon nitride.

[0060] S5: 1 g of copper-bismuth bimetallic site-polymerized carbon nitride and 100 g of titanium dioxide were added to 300 mL of methanol and stirred for 5 min, then ultrasonically treated at 20 kHz and 60 W for 1 h, and evaporated to obtain a copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst;

[0061] S6: Add 20 g of ethanol, 1 g of triethanolamine, 1 g of glycerol and 10 g of 40% alkaline silica sol with a pH of 8 to 150 mL of deionized water, stir at 60°C for 0.5 h, then add 2 g of copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst, stir at 60°C for 0.5 h, then add 5 g of polyvinyl alcohol and continue stirring for 3 h to obtain a coating solution;

[0062] S7: Immerse 3g of activated carbon honeycomb cotton in 225g of coating liquid, take out the carrier after 1 hour, and dry it at 40°C for 1 hour to obtain a photothermal catalytic filter / photothermal air purification filter.

[0063] Example 2: A method for preparing a photothermal catalytic filter without an external heat source is as follows:

[0064] S1: 1.2 g of citric acid and 5 g of copper hydroxide were dissolved in 50 mL of deionized water, stirred for 40 min, and reacted in a polytetrafluoroethylene container at 160 ° C for 5 h. The solution was then centrifuged to remove large particles, and then the solid impurities were further filtered using an aqueous microporous filter membrane. Finally, the solution was dialyzed using a dialysis bag for 6 h, and the impurities were filtered and the supernatant was collected to obtain a modified copper metal precursor solution;

[0065] S2: 13 g urea and 25 g modified copper metal precursor solution were added to 100 mL deionized water, stirred for 4 h, dried in a rotary evaporator for 1 h, then heated to 460 ° C at 6 ° C / min, calcined for 2.3 h, and cooled naturally to obtain copper metal site polymerized carbon nitride;

[0066] S3: Add 0.8 g of bismuth basic carbonate into 10 mL of deionized water and stir evenly to obtain a bismuth metal precursor solution;

[0067] S4: 1 g of copper metal site-polymerized carbon nitride and 20.5 g of methanol were added to 110 mL of deionized water. After ultrasonic treatment at 30 kHz and 65 W for 7 min, 2 mL of bismuth metal precursor solution was added dropwise while stirring. After stirring for 5 min, the mixture was first heated at 100 mW / cm 2 The solid was irradiated for 3 h at room temperature, centrifuged at 400 × g for 13 min, and washed twice with ethanol and deionized water respectively and dried at 80 ° C for 24 h to obtain copper-bismuth bimetallic site polymerized carbon nitride.

[0068] S5: 1 g of copper-bismuth bimetallic site-polymerized carbon nitride and 130 g of titanium dioxide were added to 350 mL of deionized water and stirred for 7 min, then ultrasonically treated at 30 kHz and 65 W for 1.3 h, and evaporated to obtain a copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst;

[0069] S6: Add 20 g of isopropanol, 1 g of triethanolamine, 1 g of glycerol and 10 g of 50% alkaline silica sol with a pH of 9 to 170 mL of deionized water, stir at 70°C for 0.7 h, then add 2 g of copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst, stir at 70°C for 0.7 h, then add 5 g of polyvinyl pyrrolidone and continue stirring for 3 h to obtain a coating solution;

[0070] S7: immerse 5 g of non-woven fabric in 200 g of coating liquid, take out the carrier after 1.2 hours, and dry it at 50° C. for 2 hours to obtain a photothermal catalytic filter / photothermal air purification filter.

[0071] Example 3: A method for preparing a photothermal catalytic filter without an external heat source is as follows:

[0072] S1: Dissolve 5 g of copper chloride in 50 mL of deionized water and stir evenly to obtain a common copper metal precursor solution;

[0073] S2: 18 g urea and 35 g common copper metal precursor solution were added to 100 mL deionized water, stirred for 5 h, dried in a rotary evaporator for 1 h, then heated to 550 °C at 8 °C / min, calcined for 2.8 h, and cooled naturally to obtain copper metal site polymerized carbon nitride;

[0074] S3: Add 1.2 g of bismuth chloride to 10 mL of deionized water and stir evenly to obtain a bismuth metal precursor solution;

[0075] S4: 1 g of copper metal site polymerized carbon nitride and 21 g of isopropanol were added to 130 mL of deionized water. Ultrasonic treatment was performed at 35 kHz and 65 W for 8 min. Then 2 mL of bismuth metal precursor solution was added dropwise while stirring. After stirring for 5 min, the mixture was first heated at 100 mW / cm 2 The solid was irradiated for 3 h at room temperature, centrifuged at 400 × g for 17 min, and washed twice with ethanol and deionized water respectively and dried at 80 ° C for 24 h to obtain copper-bismuth bimetallic site polymerized carbon nitride.

[0076] S5: 1 g of copper-bismuth bimetallic site-polymerized carbon nitride and 180 g of titanium dioxide were added to 450 mL of propanol and stirred for 8 min, then ultrasonically treated at 35 kHz and 65 W for 1.8 h, and evaporated to obtain a copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst;

[0077] S6: add 10g of isopropanol, 10g of propylene glycol, 1g of triethanolamine, 1g of glycerol and 10g of 60% alkaline silica sol with a pH of 10 to 180mL of deionized water, stir at 80°C for 0.8h, add 2g of copper-bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst, stir at 80°C for 0.8h, add 5g of polyethylene glycol and continue stirring for 3h to obtain a coating solution;

[0078] S7: Immerse 5g of activated carbon honeycomb cotton into 190g of coating liquid, take out the carrier after 1.8h, and dry it at 70℃ for 3h to obtain a photothermal catalytic filter / photothermal air purification filter.

[0079] Example 4: A method for preparing a photothermal catalytic filter without an external heat source is as follows:

[0080] S1: 2 g of citric acid and 5 g of copper chloride were dissolved in 50 mL of deionized water, stirred for 60 min, and reacted in a polytetrafluoroethylene container at 200 ° C for 8 h. The solution was then centrifuged to remove large particles, and then the solid impurities were further filtered using an aqueous microporous filter membrane. Finally, the solution was dialyzed using a dialysis bag for 6 h, and the impurities were filtered and the supernatant was collected to obtain a modified copper metal precursor solution;

[0081] S2: 20 g urea and 40 g modified copper metal precursor solution were added to 100 mL deionized water, stirred for 6 h, dried in a rotary evaporator for 1 h, then heated to 600 °C at 10 °C / min, calcined for 3 h, and cooled naturally to obtain copper metal site polymerized carbon nitride;

[0082] S3: Add 1.5 g of bismuth sulfate to 10 mL of deionized water and stir evenly to obtain a bismuth metal precursor solution;

[0083] S4: Add 1g of copper metal site polymerized carbon nitride and 21g of n-propanol to 150mL of deionized water, treat with 40kHz, 70W ultrasound for 10min, then add 2mL of bismuth metal precursor solution while stirring, and then stir for 5min at 100mW / cm 2 The solid was irradiated for 3 h at room temperature, centrifuged at 400 × g for 20 min, and finally the solid was washed twice with ethanol and deionized water respectively and dried at 80 ° C for 24 h to obtain copper-bismuth bimetallic site polymerized carbon nitride.

[0084] S5: 1 g of copper-bismuth bimetallic site-polymerized carbon nitride and 200 g of titanium dioxide were added to 500 mL of propanol and stirred for 10 min, then ultrasonically treated at 40 kHz and 70 W for 2 h, and evaporated to obtain a copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst;

[0085] S6: Add 5 g of ethanol, 5 g of methanol, 5 g of isopropanol, 5 g of propylene glycol, 1 g of triethanolamine, 1 g of glycerol and 10 g of 70% alkaline silica sol with a pH of 11 to 200 mL of deionized water, stir at 90° C. for 1 h, then add 2 g of copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst, stir at 90° C. for 1 h, then add 5 g of polyacrylamide and continue stirring for 3 h to obtain a coating solution;

[0086] S7: Immerse 9.4 g of non-woven fabric in 175 g of coating liquid, take out the carrier after 2 hours, and dry it at 80°C for 4 hours to obtain a photothermal catalytic filter / photothermal air purification filter.

[0087] Comparative Example 1:

[0088] Compared with Example 1, this comparative example only replaces the "photothermal air purification filter" with a "commercial filter".

[0089] Comparative Example 2:

[0090] The difference between this comparative example and Example 1 is that the performance of the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst is directly tested instead of the photothermal catalytic filter, and the toluene test method is a photothermal reactor instead of an ambient air chamber.

[0091] Comparative Example 3:

[0092] Compared with Example 1, this comparative example only replaces the "1g copper bismuth bimetallic site-polymerized carbon nitride and 100g titanium dioxide" added in the preparation process of the copper bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst with "21g copper bismuth bimetallic site-polymerized carbon nitride and 80g titanium dioxide", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a photothermal catalytic filter / photothermal air purification filter is obtained.

[0093] Comparative Example 4:

[0094] Urea, citric acid monohydrate, nitric acid and bismuth nitrate in a mass ratio of 1200:4:10:5 were added to deionized water and stirred thoroughly for 3 hours. The solution was then dried in a rotary evaporator for 1 hour. The collected solid was then placed in a round crucible with a lid, calcined at 500°C for 2 hours in a muffle furnace at a heating rate of 5°C / min and cooled naturally to obtain about 1.5g of bismuth metal site-polymerized carbon nitride. In 30mL of methanol, bismuth metal site-polymerized carbon nitride and titanium dioxide in a mass ratio of 1:200 were added, stirred for 5 minutes and then ultrasonicated for 1 hour. The mixture was then dried in a rotary evaporator for 1 hour. The reaction solid was collected to obtain a bismuth metal site-polymerized carbon nitride-titanium dioxide composite catalyst. The copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst in Example 1 was then replaced with a bismuth metal site-polymerized carbon nitride-titanium dioxide composite catalyst to prepare a photothermal catalytic filter / photothermal air purification filter.

[0095] Comparative Example 5:

[0096] Urea, citric acid monohydrate and copper nitrate in a mass ratio of 600:2:5 were added to 30 mL of deionized water and stirred thoroughly for 3 hours. The solution was then dried in a rotary evaporator for 1 hour. The collected solid was then placed in a round crucible, calcined at 500 ° C for 2 hours in a muffle furnace at a heating rate of 5 ° C / min and cooled naturally to obtain about 1.5 g of copper metal site polymerized carbon nitride. Secondly, copper metal site polymerized carbon nitride and titanium dioxide in a mass ratio of 1:100 were added to 30 mL of methanol, and ultrasonicated for 1 hour after stirring. Finally, the mixture was dried in a rotary evaporator for 1 hour, and the reaction solid was collected to obtain a copper metal site polymerized carbon nitride-titanium dioxide composite catalyst. After that, the copper bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst in Example 1 was replaced with a copper metal site polymerized carbon nitride-titanium dioxide composite catalyst to prepare a photothermal catalytic filter / photothermal air purification filter.

[0097] Comparative Example 6:

[0098] Deionized water was added to a 250 mL beaker, followed by an aqueous dispersion medium, triethanolamine, glycerol and a mechanical property improver in a mass ratio of 20:1:1:10, and then heated to 80°C in a magnetic stirrer and stirred for 0.5 h; then 2 g of the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared in Example 1 was added to the solution, followed by stirring for 0.5 h. Then 5 g of polyvinyl alcohol was slowly added and stirred for 3 h at 80°C. After sufficient stirring, the solution was viscous, and then a brush was used to apply the photothermal catalyst coating liquid on the surface of a 150 mm × 150 mm non-woven fabric; then the non-woven fabric was placed in an oven at 60°C and dried for 1 h, and the other side of the non-woven fabric was also coated with the coating liquid and dried to obtain a photothermal catalytic filter / photothermal air purification filter.

[0099] Performance testing and data analysis:

[0100] Toluene catalytic effect test:

[0101] The photothermal air purification filter prepared in the embodiment and the commercial filter of Comparative Example 1 were placed in a commercial air purifier, respectively, and then the air purifier was placed in a 120L sealed glove box. 1mL of toluene liquid was added dropwise on the heating table to completely volatilize it, and the initial concentration of toluene was stabilized for 30min, and the initial concentration was about 1200ppm. The fan and ultraviolet lamp functions of the air purifier were then turned on to start the test. The gas in the glove box was sampled every 1h, and the toluene concentration was detected using gas chromatography.

[0102] The toluene catalytic effect test method of comparative example 2 is to spread the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared in example 1 on a 6 cm 2 The bottom of the petri dish was placed in the reactor and sealed. A toluene-nitrogen-oxygen mixture (nitrogen to oxygen ratio of 3:1) was injected into the reactor by bubbling to ensure that the toluene concentration in the reactor reached 300 ppm. Full-spectrum light irradiation (300 mW / cm 2 ), and the toluene concentration in the reactor was regularly detected by chromatography during the irradiation. The toluene content was quantified by Shimadzu chromatography (GC2030).

[0103] The results of the test are as follows Figure 1 (a), where the measurement result of comparative example 1 corresponds to the commercial filter curve; the measurement result of embodiment 1 corresponds to the photothermal air purification filter A curve; the test result of comparative example 2 corresponds to the photothermal air purification filter B curve. It can be seen from the figure that the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared by the present invention has a more excellent toluene purification ability.

[0104] Methyl mercaptan catalytic effect test:

[0105] First, the photothermal air purification filter prepared in Example 4 and Comparative Example 1 and the commercial filter prepared in Comparative Example 1 were cut into 7.0 cm 2 The disc was placed at the bottom of a 35 mL transparent glass sample bottle, and the cap was then tightened to ensure a seal. Before each test, 5 mL of methyl mercaptan gas was injected into the reactor using a syringe. The gas was evaporated from the top of the propylene glycol solution of methyl mercaptan. In order to evenly distribute the gas in the reactor, it was left to stand for 5 minutes. Next, a 1 mL gas sample was extracted from the glass bottle using a syringe, and the initial concentration was determined by Shimadzu chromatography (GC2020). Then, the glass sample bottle was placed at 100 mW / cm 2The catalytic reaction started under the light condition of . During the reaction, 1 mL of gas sample was drawn with a gas sampling syringe every 5 minutes, and the concentration of methyl mercaptan was measured again by gas chromatography;

[0106] Test results such as Figure 1 (b), wherein the measurement result of comparative example 1 corresponds to the commercial filter curve; the measurement result of embodiment 1 corresponds to the photothermal air purification filter A curve; the test result of comparative example 4 corresponds to the photothermal air purification filter B curve. It can be seen from the figure that the copper bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst prepared by the present invention has a more excellent methyl mercaptan purification ability; at the same time, the bismuth metal site polymerized carbon nitride-titanium dioxide composite catalyst prepared in comparative example 4 also has a relatively excellent methyl mercaptan purification ability.

[0107] In order to ensure the stability of the photothermal catalytic filter in the methyl mercaptan reaction, a cyclic reaction stability test was carried out on the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared in Example 1. The results are as follows: Figure 6 As shown, Figure 6 (a) is the measurement result of the photothermal catalytic filter prepared in Example 1; Figure 6 (b) Figure 6 (a) The test results of the photocatalytic filter after washing and drying. Figure 6 It can be seen from (a) that after 5 cycles of reaction, the performance of the catalyst decreased significantly ( Figure 6 (a)), which is mainly due to the accumulation of dimethyl disulfide, sulfate and sulfite species on the catalyst surface. Figure 6 It can be clearly observed in (b) that the catalytic activity of the filter has been restored. In addition, due to the introduction of some water vapor, the reaction performance has been further improved, and the cycle stability has also been enhanced compared to the first cycle.

[0108] Isovaleric acid catalytic effect test:

[0109] First, the photothermal air purification filter prepared in Example 4 and Comparative Example 1 and the commercial filter prepared in Comparative Example 1 were cut into 7.0 cm 2 The disc was placed at the bottom of a 100 mL transparent glass sample bottle, and the bottle cap was then tightened to ensure a seal. Before each test, 1 mL of isovaleric acid gas was drawn from the air above the isovaleric acid solution using a syringe and injected into the transparent glass sample bottle. In order to evenly distribute the gas in the reactor and allow the non-woven fabric to reach adsorption saturation, it was left to stand for 5 minutes. Next, 1 mL of gas sample was drawn from the glass bottle using a syringe, and the initial concentration was determined by gas chromatography. Then, the glass sample bottle was placed at 100 mW / cm 2The catalytic reaction was started under the light condition of . During the reaction, 1 mL of gas sample was drawn with a gas sampling syringe every 5 minutes, and the concentration of isovaleric acid was measured again by gas chromatography.

[0110] The test results are as follows Figure 1 (c) shows that the test results of comparative example 1 correspond to the commercial filter curve; the test results of example 1 correspond to the photothermal air purification filter A curve; the test results of comparative example 4 correspond to the photothermal air purification filter B curve. It can be seen from the figure that the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared by the present invention has a more excellent isovaleric acid purification ability; at the same time, the bismuth metal site-polymerized carbon nitride-titanium dioxide composite catalyst prepared in comparative example 4 also has a relatively excellent isovaleric acid purification ability.

[0111] Acetic acid catalytic effect test:

[0112] The photothermal air purification filter prepared in Example 1 and Comparative Example 5 and the commercial filter prepared in Comparative Example 1 were placed in a commercial air purifier, and then the air purifier was placed in a 120L sealed glove box. 0.2mL of acetic acid was dropped onto the heating table to completely evaporate it, and it was left to stand for 30 minutes to stabilize the initial concentration of acetic acid. The fan and ultraviolet lamp of the air purifier were then turned on to start the test. The gas in the glove box was sampled every 1 hour, and the acetic acid concentration was detected using gas chromatography;

[0113] The test results are as follows Figure 1 (d) shows that the measurement result of comparative example 1 corresponds to the commercial filter curve; the measurement result of embodiment 1 corresponds to the photothermal air purification filter A curve; the test result of comparative example 5 corresponds to the photothermal air purification filter B curve. It can be seen from the figure that the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst and the copper metal site-polymerized carbon nitride-titanium dioxide composite catalyst prepared by the present invention both have excellent acetic acid purification capabilities.

[0114] Physical structure property characterization test of catalyst and photothermal catalytic filter:

[0115] The physical structure characterization test and elemental composition analysis of the copper-bismuth bimetallic site-polymerized carbon nitride and the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst prepared in the example were carried out by field emission scanning electron microscopy and high-resolution transmission electron microscopy. The results are as follows:

[0116] Figure 2 Field emission scanning electron microscopy images of copper-bismuth bimetallic site-polymerized carbon nitride are shown, clearly showing its bulk morphology and porous structural characteristics. Figure 3The field emission scanning electron microscope image of the copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst is presented, in which the bulk copper-bismuth bimetallic site-polymerized carbon nitride is in close contact with the spherical titanium dioxide, forming a good interface bonding, which helps to achieve a synergistic effect between the components. Figure 4 This is a high-resolution transmission electron microscope photo of copper-bismuth bimetallic site-polymerized carbon nitride. Through the contrast between light and dark, we can clearly observe its blocky porous structure. Elemental mapping analysis further reveals the uniform distribution of copper and bismuth elements in the polymerized carbon nitride, which indicates that copper-bismuth bimetallic site-polymerized carbon nitride has excellent metal dispersion, thereby enhancing its efficiency in the photothermal catalytic process. Figure 5 The photo of the photothermal catalytic filter is shown, showing the uniform distribution of the catalyst on the activated carbon honeycomb cotton. The special structure of the activated carbon honeycomb cotton gives the filter a larger specific surface area, which is conducive to full contact with the reactants, thereby promoting the photothermal catalytic air purification process.

[0117] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0118] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A photothermal catalytic filter screen that does not require an external heat source, characterized in that: The method comprises the following raw materials in parts by weight: 1 part of copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst and 10-100 parts of a carrier; The copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst is prepared from urea, a copper metal precursor solution, a bismuth metal precursor, and titanium dioxide; The copper metal precursor solution is any one of a common copper metal precursor solution and a modified copper metal precursor solution; The modified copper metal precursor solution is prepared from a copper metal precursor, citric acid, and deionized water; The copper metal precursor is any one of copper nitrate, copper hydroxide and copper chloride; The carrier is any one of activated carbon honeycomb cotton and non-woven fabric.

2. The photothermal catalytic filter without external heat source according to claim 1, characterized in that: The bismuth metal precursor is any one of bismuth nitrate, bismuth sulfate, bismuth chloride and bismuth basic carbonate.

3. The photothermal catalytic filter without external heat source according to claim 1, characterized in that: The preparation method of the copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst is as follows: Step A1: dissolving citric acid and a copper metal precursor in deionized water, stirring for 30-60 minutes, reacting in a polytetrafluoroethylene container at 150-200° C. for 4-8 hours, filtering impurities and collecting the supernatant after centrifugation to obtain a modified copper metal precursor solution; adding 5 g of the copper metal precursor to 50 mL of water, stirring evenly to obtain a common copper metal precursor solution; Step A2: adding urea and copper metal precursor solution to deionized water, stirring for 3-6 hours and then evaporating to dryness, then calcining, and naturally cooling to obtain copper metal site polymerized carbon nitride; Step A3: Add 0.5-1.5 g of bismuth metal precursor to 10 mL of deionized water and stir to obtain a bismuth metal precursor solution; Step A4: adding copper metal site polymerized carbon nitride and a sacrificial agent to deionized water, and then dripping a bismuth metal precursor solution while stirring after ultrasonic treatment, stirring for 5-10 minutes, and then sequentially irradiating and centrifuging, and finally washing and drying the solid to obtain copper bismuth bimetallic site polymerized carbon nitride; Step A5: add copper-bismuth bimetallic site-polymerized carbon nitride and titanium dioxide into a solvent and stir evenly, then perform ultrasonic treatment, and evaporate to dryness to obtain a copper-bismuth bimetallic site-polymerized carbon nitride-titanium dioxide composite catalyst.

4. The photothermal catalytic filter without external heat source according to claim 3, characterized in that: The mass ratio of citric acid, copper metal precursor and deionized water in step A1 is 1-2:5:

50.

5. The photothermal catalytic filter without external heat source according to claim 3, characterized in that: The mass ratio of urea to copper metal precursor solution in step A2 is 10-12:20-24; The heating rate during the calcination treatment in step A2 is 5-10°C / min, the calcination temperature during the calcination treatment is 450-600°C, and the calcination time during the calcination treatment is 2-3h.

6. The photothermal catalytic filter without external heat source according to claim 3, characterized in that: The amount ratio of deionized water, copper metal site polymerized carbon nitride, sacrificial agent, and bismuth metal precursor solution in step A4 is 100-150 mL: 1 g: 20-21 g: 2 mL; The sacrificial agent in step A4 is any one of ethanol, methanol, isopropanol, and n-propanol; The power of the ultrasonic treatment in step A4 is 20-40kHz, the frequency of the ultrasonic treatment is 60-70W, and the duration of the ultrasonic treatment is 5-10min; The light intensity during the irradiation treatment in step A4 is 100 mW / cm 2 The irradiation time during the irradiation treatment is 3 hours; The relative centrifugal force during the centrifugal treatment in step A4 is 400×g, and the centrifugal time during the centrifugal treatment is 10-20 min.

7. The photothermal catalytic filter without external heat source according to claim 3, characterized in that: The solvent in step A5 is any one of methanol, deionized water, ethanol, and propanol; The mass ratio of the copper-bismuth bimetallic site-polymerized carbon nitride to titanium dioxide in step A5 is 1:100-200; The power of the ultrasonic treatment in step A5 is 20-40kHz, the frequency of the ultrasonic treatment is 60-70W, and the duration of the ultrasonic treatment is 1-2h.

8. The photothermal catalytic filter without external heat source according to claim 1, characterized in that: The photothermal catalytic filter preparation method is as follows: Step S1: adding an aqueous dispersion medium, triethanolamine, glycerol and a mechanical property improver to deionized water, stirring at 60-90° C. for 0.5-1 h, adding a copper-bismuth bimetallic site polymerized carbon nitride-titanium dioxide composite catalyst, stirring at 60-90° C. for 0.5-1 h, adding an adhesive and continuing to stir at 60-90° C. to obtain a coating liquid; Step S2: immerse the carrier in the coating liquid, take out the carrier after 1-2 hours, and dry it at 40-80° C. for 1-4 hours to obtain a photothermal catalytic filter.

9. The photothermal catalytic filter without external heat source according to claim 8, characterized in that: The aqueous dispersion medium in step S1 is any one or more of ethanol, methanol, isopropanol, and propylene glycol; The mechanical property improver in step S1 is 40%-70% alkaline silica sol; The alkaline silica sol has a pH of 8-11; The adhesive in step S1 is any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, and polyacrylamide; The mass ratio of the deionized water, aqueous dispersion medium, triethanolamine, glycerol, mechanical property improver, copper-bismuth bimetallic site polymerization carbon nitride-titanium dioxide composite catalyst, and adhesive in step S1 is 150-200:20:1:1:10:2:5; The mass ratio of the carrier to the coating liquid in step S2 is 3-9.4:175-225.

10. A photothermal catalytic filter without external heat source according to any one of claims 1 to 9 and its use in removing odorous gases from the air, characterized in that: It can be used to efficiently remove toluene, methyl mercaptan, isovaleric acid, acetic acid and odorous gases from indoor air.

Citation Information

Patent Citations

  • Preparation method of air purification photocatalyst with extra-small precious metal loaded on titanium dioxide surface

    CN107930620A

  • Photocatalyst coating structure and photocatalyst-coated member

    CN116020432A